Transforming Building Renovation: A Holistic, Strategic Approach with Construction Robot Management - Ghammad, Badr; Hu, Rongbo; Bock, Thomas (International Journal of Architectural Engineering Technology, 2022)
The purpose of this research is to investigate the topic of the efficient renovation of existing buildings through construction robotics management. The main questions addressed are: How can we increase labor working conditions around construction sites? Why has the productivity of the construction industry decreased? What construction tasks require automation most? What is needed to smoothly integrate single-task construction robots (STCRs) into the established workflows? How can we optimize processes? What management system is required for STCRs? To answer these questions, thorough research has been conducted, including all identifiable resources for the area or problem. In addition, the research has been strengthened by an expert survey to define the focus areas. Further, the analysis of current established solutions and processes resulted in the presentation of a centralized platform for managing STCRs, which has been developed as part of this research. In conclusion, the strategic implications of deploying STCRs through Visual User Experience (VUX), the low-code cloud-based platform, are discussed and reinforced with a business plan to bring the product idea to life.